Viologen-based electrochromic materials and devices - Madasamy, Kanagaraj; Velayutham, David; Suryanarayanan, Vembu; Kathiresan, Murugavel; Ho, Kuo-Chuan (Journal of materials chemistry. C, Materials for optical and electronic devices, 2019)
Considerable interest is raised by organic materials owing to their exceptional performance in electronic and optoelectronic applications. Among these, electrochromic materials (EC) that can be switched between a distinct color and a bleached state exhibiting high contrast, multicolor and improved long-term stability are attractive in the fabrication of electrochromic devices (ECDs). Ionic materials, in particular, have received persistent attention owing to their tunable optical and electronic properties. 4,4′-Bipyridinium salts, commonly called viologens (V 2+ ), are a well-recognized class of electrochromic materials that exhibit three reversible redox states, namely, V 2+ (dication, pale yellow colored/colorless) ↔ V + &z.rad; (radical cation, violet/blue/green) ↔ V 0 (neutral, colorless). The electrochromic properties of these materials can be modulated by varying the nitrogen substituents on the pyridyl 'N'; also, besides this, varying the counter ions with specific functionalities has been shown to enhance the electrochromic behavior, such as switching time, cycling stability and device performance. Although ECDs based on viologens are well regarded for their low operational voltages, they exhibit certain disadvantages such as low cycle life and poor efficiency of the device in the long term. Extensive efforts have been made to fine tune the EC properties of viologens, either through alteration or by adding suitable electrochromic counter electrode materials, which includes the incorporation of conducting polymers in the device set-up and/or the addition of complementary redox species. Optimization of the device parameters has shown that the addition of such external agents has a positive effect on the overall device performance. This review describes recent developments in the synthesis of viologen-based electrochromes with co-redox species and their ECD performance. This review describes recent developments relating to the synthesis of viologen-based electrochromes with co-redox species and their ECD performance.